Long noncoding RNA RUSC1-AS1 promotes tumorigenesis in cervical cancer by acting as a competing endogenous RNA of microRNA-744 and consequently increasing Bcl-2 expression. Issue 10 (18th May 2020) - Guo, Qizhen; Zhang, Qin; Lu, Lianwei; Xu, Yanping
ABSTRACT: The expression of a long noncoding RNA termed RUSC1-AS1 is dysregulated in breast cancer and laryngeal squamous cell carcinoma, and this dysregulation affects various tumor-associated biological processes. To our knowledge, the expression status and detailed roles of RUSC1-AS1 in cervical cancer as well as its regulatory mechanisms of action remain unknown. Therefore, the objectives of this study were to measure RUSC1-AS1 expression in cervical cancer, investigate the effects of RUSC1-AS1 on cervical cancer cells, and identify the mechanism underlying these effects. Herein, RUSC1-AS1 was found to be highly expressed in cervical cancer tissues and cell lines. High RUSC1-AS1 expression significantly correlated with the International Federation of Gynecology and Obstetrics (FIGO) stage, lymph node metastasis, and shorter overall survival among the patients with cervical cancer. Functional assays revealed that interference with RUSC1-AS1 expression suppressed cervical cancer cell proliferation, migration, and invasion in vitro; induced apoptosis in vitro; and impeded tumor growth in vivo. In addition, RUSC1-AS1 was demonstrated to act as a competing endogenous RNA of microRNA-744 (miR-744) and consequently increase B-cell lymphoma 2 (Bcl-2 or BCL2) expression levels in cervical cancer cells. Furthermore, either inhibition of miR-744 or restoration of Bcl-2 expression neutralized the effects of the RUSC1-AS1 silencing on the malignant characteristics of cervical cancer cells. Thus, RUSC1-AS1 promotes the aggressiveness of cervical cancer in vitro and in vivo by upregulating miR-744–Bcl-2 axis output. The RUSC1-AS1 –miR-744–Bcl-2 pathway may be involved in cervical cancer pathogenesis and could serve as a novel target for anticancer therapies.